2015
DOI: 10.1080/14786419.2015.1057728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemical constitute, fatty acids and antioxidant activity of the fruit and seed of sea buckthorn (Hippophae rhamnoidesL.) grown wild in Iran

Abstract: In this investigation, the chemical compositions of berries from sea buckthorn were studied. The amount of ascorbic acid and β-carotene determined by HPLC was 170 mg/100 g FW and 0.20 mg/g FW, respectively. Total phenols, anthocyanins, acidity and total soluble solids (TSS) contents were 247 mg GAE/100 g FW, 3 mg/L (cyanidin-3-glucoside), 5.32% and 13.8%, respectively. Fruit antioxidant activity determined by the ferric reducing ability of plasma (FRAP) method was 24.85 mM Fe/100 g FW. Results confirmed the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The present study, however, performed an extensive evaluation of 18 different barberry genotypes native to Iran, in order to provide valuable data and new insights useful for planning breeding strategies, as well as for selecting species with high phenolic contents for producing natural antioxidants for pharma food products. Some researchers suggest that the TPC of plants is influenced by various factors such as genetic background, longitude, sampling location, pre‐harvest and post‐harvest conditions and maturity stage at harvest …”
Section: Resultssupporting
confidence: 82%
“…The present study, however, performed an extensive evaluation of 18 different barberry genotypes native to Iran, in order to provide valuable data and new insights useful for planning breeding strategies, as well as for selecting species with high phenolic contents for producing natural antioxidants for pharma food products. Some researchers suggest that the TPC of plants is influenced by various factors such as genetic background, longitude, sampling location, pre‐harvest and post‐harvest conditions and maturity stage at harvest …”
Section: Resultssupporting
confidence: 82%
“…Hippophae rhamnoides L., is an edible medicinal plant used as a medicinal agent in traditional Chinese medicine and Tibetan medicine. Hippophae rhamnoides L., possesses biological properties of anti-tumor, antiinflammation, anti-oxidation, hypoglycemia and hypotriglyceridemia [21][22][23][24], whereas kaempferol and kaempferide were suggested to be active in anti-cancer, anti-inflammation, anti-oxidation, anti-diabetes, anti-obesity and neuroprotection [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some studies reported that hexanol and other ma-jor derivatives found in various extracts, such as pomegranates, mung bean, ripe coffee beans and soybeans, are responsible for anti-oxidant properties (54)(55)(56). In the case of saturated fatty acids, extracts of Annona muricata L. Labisia pumila Benth, sea buckthorn, and Trifolium species also exhibited anti-oxidant activity owing to large percentages of n-hexadecanoic acid and octadecanoic acid (57)(58)(59)(60). In addition, fatty acids such as n-hexadecanoic acid and octadecanoic acid were reported to exert effects against oxidative stress (61,62).…”
Section: Resultsmentioning
confidence: 99%